When Literary ‘Arabiya Adopted for A Religious Mission: The Quran and the Expansion of the Arabic Poetic Koine - Ikhwan, Munirul (Al-Jami'ah Research Centre, 2024)
Much has been discussed regarding the nature of the language of the Quran, whose vocabulary, according to Muslim belief, is meaningfully chosen and perfectly structured, a contention that underlies the doctrine of its inimitability (iʻjāz). For the majority of Muslims, the debates over the nature of the Quran’s language have been relatively conclusive; it is the most fluent Arabic, derived mainly from the Quraysh dialect. Meanwhile, modern scholars working under the umbrella of critical philology and history refuse to take the above theory for granted. They link the language of the Quran with the idea of the literary ʻArabiyya, a poetic koine that was constructed much more within the culture of the pre-Islamic Arabs living in the area of Najd. This article exhibits theoretical discussions that may shed light on a new perspective of the theme. This study argues that the literary ʻArabiyya is adopted by the Quran as a mode of discourse to introduce a monotheistic message to its first audience. By doing so, the Quran works within the literary tradition of Arabic rhetoric, which was highly valued within the pre-Islamic Arab culture. As the Quran aimed at promoting monotheism by convincing as many followers as possible, it creatively expanded the boundaries of the literary ʻArabiyya by introducing sabʻah aḥruf (variant styles of reading), through which it was able to address more and more audience.[Banyak yang telah menulis tentang hakikat bahasa al-Quran, yang menurut kepercayaan Muslim, kosakatanya dipilih secara bermakna dan terstruktur dengan sempurna sehingga menjadikannya mukjizat yang mendasari doktrin tentang kemustahilan untuk menandingi. Bagi mayoritas Muslim, perdebatan mengenai hakikat bahasa al-Quran relatif sudah selesai, yakni sebagai bahasa Arab yang paling fasih, yang sebagian besar berdasarkan dialek Quraisy. Sementara itu, para sarjana modern dengan disiplin sejarah dan filologi kritis menolak untuk menerima teori di atas begitu saja. Mereka mengaitkan bahasa al-Quran dengan koine puitis, sebagai bagian dari Arab sastrawi, yang lebih banyak terbentuk dalam budaya Arab pra-Islam di wilayah Najd. Artikel ini menyuguhkan diskusi teoretis untuk menjelaskan perspektif baru dalam pembahasan tema tersebut. Penulis berpendapat bahwa unsur Arab sastrawi diadopsi oleh al-Quran sebagai sebuah cara berwacana dalam memperkenalkan pesan monoteistik kepada audiens pertamanya. Dengan demikian, al-Quran bekerja dalam tradisi retorika sastra, yang sangat dihargai dalam budaya Arab pra-Islam. Karena bertujuan untuk mempromosikan monoteisme dan menarik sebanyak mungkin pengikut, al-Quran secara kreatif memperluas cakupan Arab sastrawi dengan memperkenalkan konsep sab‘ah aḥruf (variasi gaya bacaan), yang dapat dipakai untuk menjangkau lebih banyak pembaca.]